Дослідження осідань підземних конструкцій промислового цеху від дії динамічних навантажень його обладнання - Aleksandrovych, Vadym (Збірник наукових праць Галузеве машинобудування будівництво, 2019)
The article is devoted to the issue of research of the soil basement vibrocreep negative impact, which takes place underdynamic loads. The results of on-site measurements of industrial facility underground structures forced dynamic vibrationsparameters have been presented. The influence of the dynamic vibrations value on the development of underground cablechannel precast concrete units uneven settlement has been analyzed. The interrelation between the value of the channel builtupconstruction settlement at the point of measurement and the amplitude of forced vibrations at this point has been determined.
Keywords: віброповзучість; ґрунтова основа; фундамент; нерівномірне осідання; динамічне навантаження; я, амплітуда коливань